The Influences of Job Design, Competence and Rewards on Job Satisfaction and Employee Performance of PDAM Delta Tirta Sidoarjo Regency - Rosalina Ayu Wulandari; Ida Aju Brahmasari; Ida Aju Brahma Ratih (PT Inovasi Pratama Internasional, 2024)
The Indonesian government has the responsibility to design and implement policies that integrate economic, social and environmental aspects in realizing sustainable development. The government always strives to manage existing natural resources (SDA) for the welfare of the Indonesian people as a form of the government's alignment with the interests of society. This study aims to determine and analyze the influence of job design, competency and reward on job satisfaction and employee performance of PDAM Delta Tirta Sidoarjo Regency. The approach used in this research is a quantitative approach. The sampling technique used was proportionate random sampling, the research sample amounted to 172 respondents. Data collection using questionnaires distributed to 301 employees. The collected data were analyzed using structural equation modeling (SEM) analysis techniques using statistical software tools, namely Amos 24. The results showed that Job design affects on Job satisfaction; Job design affects employee performance; Competency affects Job satisfaction; Competency affects employee performance; Reward affects Job satisfaction; Reward System has no effect on employee performance; Job Satisfaction affects employee performance.